Individual Factors Associated with Health-Related Quality of Life in Facial Cutaneous Squamous Cell Carcinoma—A Pilot Study - Oliver Wagendorf; Forogh Miethe; Jonas Wüster; Meikel Vesper; Steffen Koerdt; Carsten Rendenbach; Max Heiland; Susanne Nahles; Norbert Neckel (Craniomaxillofacial Trauma & Reconstruction, 2026)
Purpose: Facial expressions and aesthetics are vital for communication, self-expression, and social interaction. Therefore, this study aimed to evaluate the impact of localization and size of facial cutaneous squamous cell carcinoma (cSCC) on changes in perceived pre- and postoperative health-related quality of life (HR-QoL). Methods: This retrospective study included patients who had undergone surgery for facial cSCC. Size, localization and stage were assessed. Pre- and postoperative HR-QoL were evaluated using the Skindex-29. Statistical analyses, including descriptive statistics, the X2 Test, Wilcoxon Test, and repeated-measures ANOVA, were performed to analyze demographic data, tumor characteristics, and changes in HR-QoL. Results: Forty patients (mean age of 78.5 years) were included. Postoperatively, significant improvements were observed in the overall, emotional, and symptomatic HR-QoL. Tumor dimensions had an impact on presurgical emotional distress. For tumor sizes from 6 to 15 mm, significant release in symptom burden and improvement in general HR-QoL were observed. While women experienced notable improvement only in emotional distress, men also exhibited improvement in symptoms, and overall HR-QoL. All age groups showed improvements in emotional distress, symptoms and overall HR-QoL. No significant differences were found in terms of age or localization. Conclusions: This study suggests that sex, tumor localization, and tumor size may interact in influencing postoperative HR-QoL outcomes in patients with cSCC. While surgical treatment by experienced specialists was associated with an overall improvement in HR-QoL following successful tumor eradication, these findings should be interpreted with caution given the limited sample size. The results indicate that surgery remains an important first-line treatment option, particularly for medium-sized tumors. In this cohort, TNM classification was not associated with postoperative HR-QoL changes; however, interpretation is limited by the predominance of early-stage tumors. Further studies with larger patient populations are required to confirm these observations and to better elucidate the relationship between clinical staging and HR-QoL outcomes.